Spot Welding of 6061 Aluminum Alloy by Friction Stir Spot Welding Process - Tashkandi, M. A.; Al-jarrah, J. A.; Ibrahim, M. (Engineering, Technology & Applied Science Research, 2017)
This study was focused on the effect of welding parameters on the lap-shear fracture load of the welded joints prepared by friction stir spot welding. Four different weld parameters were analyzed: rotational speed, dwell time, pin length and shoulder size of the welding tool. It was found that the lap-shear fracture load increases with an increase of the welding parameters to a limited value and decreases with further increase. The strong welded joints failed under nugget-pull out fracture.